Academic Service Quality And Learning's Influence On Student Satisfaction In The IAIN Curup Graduate Program - Alfaroq, Fikri; Warlizasusi, Jumira; Saputra, Hasep (Graduate Program Magister Manajemen Pendidikan, 2022)
This research is motivated because there are study programs in the IAIN Curup postgraduate program that have not been nationally accredited. However, in 2019 this accreditation problem can be overcome with the issuance of B accreditation for the MPI, PAI, and HKI programs, while the BKPI study program is still at minimal accreditation, as a study program that has just received an establishment permit. Another problem is that there are some students who are dissatisfied with the postgraduate services of IAIN Curup, especially the performance of several lecturers. There are lecturers who do not provide information regarding absenteeism, and some students admit that they tend to experience difficulties when conducting thesis guidance. This study aims to determine the quality of academic and learning services on student satisfaction of the IAIN Curup postgraduate program. The sample used was 30 respondents from each study program in the IAIN Curup postgraduate program with non-probability sampling. The data analysis technique used is linear regression analysis. The results showed that the variables of academic service and learning had a significant effect on student satisfaction of the IAIN Curup postgraduate program. The results of this study are expected to provide a positive significance for academic services and the learning process so that students can complete their studies on time and students become more total in carrying out the learning process.